Replacing iron‐folic acid with multiple micronutrient supplements among pregnant women in Bangladesh and Burkina Faso: costs, impacts, and cost‐effectiveness. Issue 1 (27th May 2019) - Engle‐Stone, Reina; Kumordzie, Sika M.; Meinzen‐Dick, Laura; Vosti, Stephen A.
Abstract: Consumption of multiple micronutrient supplements (MMS) during pregnancy offers additional benefits compared with iron‐folic acid (IFA) supplementation, but the tablets are more expensive. We estimated the effects, costs, and cost‐effectiveness of hypothetically replacing IFA supplements with MMS for 1 year in Bangladesh and Burkina Faso. Using baseline demographic characteristics from LiST and effect sizes from a meta‐analysis, we estimated the marginal effects of replacing IFA with MMS on mortality, adverse birth outcomes, and disability‐adjusted life years (DALYs) averted. We calculated the marginal tablet costs of completely replacing MMS with IFA (assuming 180 tablets per covered pregnancy). Replacing IFA with MMS could avert over 15, 000 deaths and 30, 000 cases of preterm birth annually in Bangladesh and over 5000 deaths and 5000 cases of preterm birth in Burkina Faso, assuming 100% coverage and adherence. We estimated the cost per death averted to be US$175–185 in Bangladesh and $112–125 in Burkina Faso. Cost per DALY averted ranged from $3 to $15, depending on the country and consideration of subgroup effects. Our estimates suggest that this policy change would cost‐effectively save lives and reduce life‐long disabilities. Improvements in program delivery and supplement adherence would be expected to improve the cost‐effectiveness of replacing IFA with MMS.